2018
DOI: 10.1039/c7fo02058a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endocrine disruption potential of essential oils of culinary herbs and spices involving glucocorticoid, androgen and vitamin D receptors

Abstract: Essential oils (EOs) of culinary herbs and spices are consumed on a daily basis. They are multicomponent mixtures of compounds with already demonstrated biological activities. Taking into account regular dietary intake and the chemical composition of EOs, they may be considered as candidates for endocrine-disrupting entities. Therefore, we examined the effects of 31 EOs of culinary herbs and spices on transcriptional activities of glucocorticoid receptor (GR), androgen receptor (AR) and vitamin D receptor (VDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Also, non-genomic effects of vitamin D, characterized by rapid activation followed by other complex pathways of intracellular signal transduction after binding of 1,25(OH)D 3 to its non-nuclear receptor (Losel et al 2003; Girgis et al 2013; Owens et al 2015) have been reported. Interestingly not only vitamin D itself, but also essential oils (caraway, coriander, dill, ginger, lemongrass, oregano, spearmint, thyme, turmeric and verveine) exhibit the ability to modulate VDR activity (Bartonkova et al 2018). Intriguingly, essential oils of turmeric, oregano, dill, caraway, verveine and spearmint augmented the activity of both VDR and glucocorticoid receptor (GR) (Bartonkova et al 2018).…”
Section: Vdr In Musculoskeletal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, non-genomic effects of vitamin D, characterized by rapid activation followed by other complex pathways of intracellular signal transduction after binding of 1,25(OH)D 3 to its non-nuclear receptor (Losel et al 2003; Girgis et al 2013; Owens et al 2015) have been reported. Interestingly not only vitamin D itself, but also essential oils (caraway, coriander, dill, ginger, lemongrass, oregano, spearmint, thyme, turmeric and verveine) exhibit the ability to modulate VDR activity (Bartonkova et al 2018). Intriguingly, essential oils of turmeric, oregano, dill, caraway, verveine and spearmint augmented the activity of both VDR and glucocorticoid receptor (GR) (Bartonkova et al 2018).…”
Section: Vdr In Musculoskeletal Systemmentioning
confidence: 99%
“…Interestingly not only vitamin D itself, but also essential oils (caraway, coriander, dill, ginger, lemongrass, oregano, spearmint, thyme, turmeric and verveine) exhibit the ability to modulate VDR activity (Bartonkova et al 2018). Intriguingly, essential oils of turmeric, oregano, dill, caraway, verveine and spearmint augmented the activity of both VDR and glucocorticoid receptor (GR) (Bartonkova et al 2018). The concentrations of essential oils used in this study are naturally occurring in foods and drinks (Usjak et al 2017).…”
Section: Vdr In Musculoskeletal Systemmentioning
confidence: 99%
“…It seems to be very difficult to declare, that e.g. phytoestrogens are beneficial and bisphenol A is harmful, as the decision is dependent on the aspects and so many new molecules appeared as exohormone, that almost impossible at present to decide, what will be evolutionarily useful without acute destroying effect, or acutely useful with evolutionarily harmful effects [29]. The fact is: in contrast to the earlier times, exohormones must be considered and from this aspect the so-called vitamins and so-called endocrine disruptors are in the same category.…”
Section: What Is a Hormone?mentioning
confidence: 99%
“…Bartonkova et al . [ 24 ] reported the effective performance of herbal extracts on glucocorticoid based receptors, which exhibited anti-hypertensive, anti-fungal, anti-microbial and anti-inflammatory properties, boosting the immune response against the harmful viral infections. Similarly, Kumar et al .…”
Section: Introductionmentioning
confidence: 99%